Allergic Contact Dermatitis with Underlying Disease Seborrhoeic Dermatitis: A Case Report - Miranti, Umi; Yoga, R. Ristianto; Nuridah, Ayu Lilyana; Amien, M. Irsyad; Misturiansyah, Nurrul Izza (Faculty of Medicine, Universitas Jember, 2024)
Seborrhoeic dermatitis is a skin disease with erythropopulosquamous morphology in areas of the skin that are rich in sebaceous glands such as the folds, scalp and face. The prevalence of seborrheic dermatitis worldwide is only around 5%, but the incidence of the non-inflammatory type of this disease (dandruff) reaches 50%. Seborrheic dermatitis can appear together with other types of dermatitis such as contact dermatitis, such as allergic contact dermatitis or irritant contact dermatitis. In this case, we will describe the incidence of seborrheic dermatitis accompanied by allergic contact dermatitis. Diagnosis in cases of seborrheic dermatitis accompanied by contact dermatitis must be carried out appropriately according to the subjective data and efflorescence obtained. The correct diagnosis influences appropriate management and a better prognosis for the patient. Keywords: Seborrhoeic dermatitis, allergic contact dermatitis